Picture perfect peaks: comprehension of inferential techniques in visual narratives. (23rd December 2022) - Klomberg, Bien; Cohn, Neil
Abstract: The ability to reconstruct a missing event to create a coherent interpretation – bridging inference – is central to understanding both real-world events and visual narratives like comics. Most previous work on visual narrative inferencing has focused on fully omitted events, yet few have compared inference generation when climactic events become replaced with a panel employing numerous inferential techniques (e.g., action stars or onomatopoeia). These techniques implicitly express the unseen event while balancing several underlying features that describe their informativeness. Here, we examine whether processing and inference resolution differ across inferential techniques in two self-paced reading experiments. Experiment 1 directly compared five distinct types, and Experiment 2 explored the effect of combining techniques. In both experiments, differences in processing arise both between inferential techniques themselves, and at subsequent panels allowing the bridging inference to be resolved. Analysis of inferential features suggested that the explicitness of the inferential technique led to greater demand in processing, which later facilitated inference generation and comprehensibility. The findings reinforce the necessity of discussing the diversity of narrative patterns motivating bridging inferences within visual narratives.